Cyclic Fatigue Life of Two Single File Engine-Driven Systems in Simulated Curved Canals - Nabavizadeh, Mohammadreza; Sedigh-Shams, Mahdi; Abdolrasoulnia, Sara (Iranian Endodontic Journal, 2019)
Introduction: This study aimed to evaluate the cyclic fatigue resistance of two single file engine-driven instruments, Reciproc and NeoNiTi, in simulated root canals. Methods and Materials: Two groups of 15 NiTi endodontic instruments with an identical tip size of 0.25 mm were tested: Reciproc R25 (group A) and NeoNiTi A1 (group B). Cyclic fatigue testing was performed in a stainless steel artificial canal. The simulated canals had a 60° angle and 5-mm radius curvature. The Reciproc instruments were operated using the preset program on torque control electric motor specific for the Reciproc instruments, while the NeoNiTi instruments were operated using the manufacturer recommendation. All instruments were rotated until fracture occurred, and the number of cycles to fracture (NCF) and the length of the fractured tip were recorded and registered. Means and standard deviations of NCF and fragment length were calculated for each system and data were subjected to Student’s t test (P<0.05). Results: A statistically significant difference (P<0.05) was noted between Reciproc and NeoNiTi instruments. NeoNiTi A1 instruments were associated with a significantly higher mean NCF as compared to Reciproc R25 instruments (833±176 vs. 318±87 NCF). There was no significant difference (P>0.05) in the mean length of the fractured fragments between the instruments. Conclusion: NeoNiTi instruments were associated with a significantly higher cyclic fatigue resistance than Reciproc instruments. Keywords: Cyclic Fatigue; NeoNiTi; Reciproc; Single-File System